High speed networks - Boisseau, M. (Marc) (Wiley series in communication and distributed systems, 1994)
This text covers factors relating only to the transmission of information-not its processing. Presents the characteristics of standardized local-area networks-contention bus, token ring and token bus-describing FDDI protocol along with several high-speed LAN projects. Identifies the particular role of metropolitan networks, explaining the DQDB protocol as well as SMDS and CBDS services. Discusses SDH, switching techniques, ATM, wideband ISDN, mechanisms used in bridges and routers and much more.